2021
DOI: 10.1108/aaaj-09-2020-4925
|View full text |Cite
|
Sign up to set email alerts
|

Exploring accountability of Australia and New Zealand's temporary labour mobility programmes in Samoa using a talanoa approach

Abstract: PurposeTemporary labour mobility programmes (TLMPs) are initiated by high-income nations to fill their labour demands by offering temporary work opportunities to migrants from low-income nations. TLMPs also seek to contribute to economic development in workers' home countries. This paper aims to assess the accountability of New Zealand's Recognised Seasonal Employer (RSE) Scheme and Australia's Seasonal Worker Programme (SWP) in reaching their economic development objectives in one sending nation, Samoa.Design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Previous studies have shown that SWP employers prefer workers from rural areas of PICs, and look to build relationships of trust with workers from particular areas who may return for several seasons (Bailey & Rereman, 2019). However, there are equity considerations around allowing workers to return for many seasons, because others may miss out on the income‐earning potential offered by SWP participation (Doan et al., 2020; Perkiss et al., 2022).…”
Section: The Australia‐pacific Agriculture and Circular Migration Nexusmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that SWP employers prefer workers from rural areas of PICs, and look to build relationships of trust with workers from particular areas who may return for several seasons (Bailey & Rereman, 2019). However, there are equity considerations around allowing workers to return for many seasons, because others may miss out on the income‐earning potential offered by SWP participation (Doan et al., 2020; Perkiss et al., 2022).…”
Section: The Australia‐pacific Agriculture and Circular Migration Nexusmentioning
confidence: 99%
“…Previous studies have shown that SWP employers prefer workers from rural areas of PICs, and look to build relationships of trust with workers from particular areas who may return for several seasons . However, there are equity considerations around allowing workers to return for many seasons, because others may miss out on the income-earning potential offered by SWP participation (Doan et al, 2020;Perkiss et al, 2022). At the intersection of Pacific labour mobility, agricultural production, and food security initiatives, there is an as yet largely underexplored opportunity to understand how workers involved in circular migration, via labour mobility programs between Australia and PICs, participate in agricultural knowledge flows (Dun & Klocker, 2017).…”
Section: The Australia-pacific Agriculture and Circular Migration Nexusmentioning
confidence: 99%
“…The talanoa method as a form of engagement is described by Perkiss (2022) as a research methodology that can be applied as a theory as well as a method. It is commonly used for research in the Pacific Islands region and is amongst the suite of qualitative research approaches used in interdisciplinary studies.…”
Section: Talanoa As Methodsmentioning
confidence: 99%
“…It is commonly used for research in the Pacific Islands region and is amongst the suite of qualitative research approaches used in interdisciplinary studies. It is a traditional Pacific practice about connecting people and storytelling, which belongs to an interpretive-constructivist paradigm (Perkiss, 2022). The talanoa method as identified by Vaioleti (2006) is a shared act of social, political, and critical conversation conducted for a purpose.…”
Section: Talanoa As Methodsmentioning
confidence: 99%
See 1 more Smart Citation